Women Sexual Oppression in Wenda Koiman’s Curahan Hati Sang SPG (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2019)
In the world of Indonesian literature, today women and sex are two very important issues: many male writers often use sex as a trendy theme of literary work. Many male authors who do not leave sex as their central theme from year to year. Therefore, this paper tries to expose (1) how is the form of sexual oppression of SPG’s body in this pop novel? (2) how is the author's perspective on female sexuality raised through the SPG’s story reflected in this pop novel (3) how to do the effects of sexuality discourse faced by SPG in this pop novel?. It uses descriptive qualitative. Data are taken from all descriptive concerning SPG body appearance to understand the narrative meaning of the body. Data are taken from all descriptive concerning SPG body appearance to understand the narrative meaning of the body. Women will be moved to choose instant success where they believe that the body beauty possessed by them will be able to bring them to the gates of success without having to do various difficult ways to get that success. Women now want instant success. They don't have to work hard, don't need to work, it's not important to study diligently. The most important thing is only a beautiful decorated face, attractive appearance and graceful attitude. So that women like this are the same as electronic devices that quickly experience the ups and downs of their models and slowly disappear in circulation.